Profil Degradasi Rumput Lapangan yang Disuplementasi dengan Bungkil Kedelai dan Daun Lamtoro - Susi Dwi Widyawati; Wara Pratitis Sabar Suprayogi (Caraka Tani: Journal of Sustainable Agriculture, 2007)
The esperiment was conducted to evaluate the effect of dietary addition of feed supplement on ruminal degradation of native grass with nylon bag technique or in sacco technique. The trial was a completely randomized design experiment of a 4 replicates on 2 rumen fistulateed cattles. Native grass was added with 4 kind of seed supplements as a growth promoting feed supplement (GPFS) with different feeds composition, they were consist of iso Nitrogenous and iso Carboneous. GPFS A consist of soybean meal and ketepeng leaf, GPFS B consist of soybean meal and lemuru fish oil, GPFS C consist of Leucaena leaf and ketepeng leaf and GPFS D consist of Leucaena leaf and lemuru fish oil. Four ration were incubated in the rumen for 0, 2, 4, 8, 12, 24, 32, 48, and 72 hours. Both dry matter (DM) and organic matter (OM) disappearance of native grass were not significantly affected by different feed supplement. Also, DM, OM, and crude fiber (CF) during 72 hours incubation were not affected by addition of feed supplements. Four kind of feed supplements had the similar potential to improve the ruminal environment and ruminal degradation